Prospective energy content assessment of waste biomass and polymer via preliminary analysis - Seah, Chiun Chao; Habib, Saiful Hafiz; Hafriz, R.S.R.M.; Shamsuddin, A.H.; Razali, N.M.; Salmiaton, A. (Elsevier, 2024)
Energy generation from waste biomass offers a promising solution for reducing greenhouse gas emissions and promoting a circular economy. This study investigates the energy potential of various organic materials, including rice husk, soybean, lemon myrtle, waste coffee ground, and empty fruit bunch, co-pyrolysed with HDPE at 500 °C and 50:50 blending ratio for 1 h. Proximate, ultimate, and thermogravimetric analyses were conducted up to 700 °C to determine elemental composition and thermal behaviour. Dulong's formula, modified Dulong's formula, and Vandralek's equation were utilised to assess energy content. Proximate analysis revealed rice husk as the highest in volatile matter (73.08 %), while waste coffee ground had the lowest (32.0 %), and HDPE showed 89.90 %. Ultimate analysis showed organic waste carbon ranges from 25.59 % to 48.75 %, and HDPE at 82.24 %. Pyrolysis reactions yielded distinct distributions of bio-oil, char, and gas, with empty fruit bunch producing the highest oil percentage (26.49 %), lemon myrtle yielding the highest gas (31.07 %), and waste coffee ground favouring char production (74.89 %). Discrepancies in heating values were observed, with Dulong's formula underestimating values for rice husk, soybean, and waste coffee ground (−10 % to −35 %) and slightly overestimating for lemon myrtle, empty fruit bunch, and HDPE (1 %–25 %). The modified Dulong formula accentuated underestimations, particularly for soybean (−451 %). The Vandralek formula showed positive error ranges (8 %) for biomass samples but underestimated HDPE. This study underscores biomass and HDPE as viable alternatives to conventional energy sources and suggests avenues for future research while highlighting environmental benefits.